PaTH: towards a learning health system in the Mid-Atlantic region. (12th May 2014) - Amin, Waqas; Tsui, Fuchiang (Rich); Borromeo, Charles; Chuang, Cynthia H; Espino, Jeremy U; Ford, Daniel; Hwang, Wenke; Kapoor, Wishwa; Lehmann, Harold; Martich, G Daniel; Morton, Sally; Paranjape, Anuradha; et al.
Abstract: The PaTH (University of Pittsburgh/UPMC, Penn State College of Medicine, Temple University Hospital, and Johns Hopkins University) clinical data research network initiative is a collaborative effort among four academic health centers in the Mid-Atlantic region. PaTH will provide robust infrastructure to conduct research, explore clinical outcomes, link with biospecimens, and improve methods for sharing and analyzing data across our diverse populations. Our disease foci are idiopathic pulmonary fibrosis, atrial fibrillation, and obesity. The four network sites have extensive experience in using data from electronic health records and have devised robust methods for patient outreach and recruitment. The network will adopt best practices by using the open-source data-sharing tool, Informatics for Integrating Biology and the Bedside (i2b2), at each site to enhance data sharing using centrally defined common data elements, and will use the Shared Health Research Information Network (SHRINE) for distributed queries across the network.